Evaluation of Meniscal Load and Load Distribution in the Canine Stifle after Tibial Plateau Levelling Osteotomy with Postoperative Tibia Plateau Angles of 6 and 1 Degrees - Schmutterer, Johannes Maximilian; Augat, Peter; Greinwald, Markus; Meyer-Lindenberg, Andrea (Veterinary and Comparative Orthopaedics and Traumatology, 2021)
Objective The aim of the study was to investigate the kinetic and kinematic changes in the stifle after a tibial plateau levelling osteotomy (TPLO) with a postoperative tibia plateau angle (TPA) of either 6 or 1 degrees.Study Design Biomechanical ex vivo study using seven unpaired canine cadaver hindlimbs from adult Retrievers.Hinge plates were applied and a sham TPLO surgery was performed. Motion sensors were fixed to the tibia and the femur for kinematic data acquisition. Pressure mapping sensors were placed between femur and both menisci. Thirty per cent bodyweight was applied to the limbs with the stifle in 135 degrees of extension. Each knee was tested with intact cranial cruciate ligament (CCL), deficient CCL, 6 degrees TPLO and 1degree TPLO.Results Transection of the CCL altered kinematics and kinetics. However, comparing the intact with both TPLO set-ups, no changes in kinematics were detected. After 1 degree TPLO, a significant reduction in the force acting on both menisci was detected (p = 0.006).Conclusion Tibial plateau levelling osteotomy restores stifle kinematics and meniscal kinetics after transection of the CCL ex vivo. The contact force on both menisci is reduced significantly after TPLO with a TPA of 1 degree. Increased stifle flexion might lead to caudal tibial motion.
Keywords: stifle; cranial cruciate ligament; kinetics; TPLO; biomechanics; tibia plateau angle